Optical fiber sensor and preparation method thereof
By employing a single-mode fiber-tapered coreless fiber-single-mode fiber splicing structure and a cascaded FP cavity structure in the fiber optic sensor, combined with a metal reinforcement layer and a sensitive material coating, the shortcomings of existing fiber optic sensors in terms of sensitivity and cross-interference are solved, achieving high-sensitivity multi-parameter synchronous measurement and improved stability, making it suitable for industrial monitoring and biomedical applications.
Patent Information
- Application Number
- CN202511425184.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2026-01-16
AI Technical Summary
Existing fiber optic sensors have room for improvement in terms of sensitivity, anti-interference capability, and stability, making it difficult to meet the needs of industrial monitoring and biomedical fields for detection accuracy and simultaneous measurement of multiple parameters.
A single-mode fiber-tapered coreless fiber-single-mode fiber splicing structure is adopted, combined with a cascaded FP cavity structure, a metal reinforcement layer and a sensitive material coating, including a silver film, a gold nanorod array, PDMS and a PVA film. Through evanescent field effect, surface plasmon resonance effect and regional selective response, sensitivity amplification and cross-interference reduction are achieved.
It achieves high-sensitivity detection of fiber optic sensors, enabling simultaneous measurement of temperature, humidity, and refractive index, reducing cross-interference between parameters, and improving structural stability, making it suitable for miniaturized applications.
Smart Images

Figure CN121346860A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of optical fiber sensing, in particular to an optical fiber sensor and a preparation method thereof. BACKGROUND
[0002] With the continuous development of optical fiber communication technology, optical fiber sensing technology has also been rapidly improved. In the past four decades, laser technology and low-loss optical fiber manufacturing have gradually matured in the optical industry, and various complex optical fiber sensor structures and new materials have been applied to the field of optical fiber sensing. Optical fiber sensors use optical fibers to transmit information, have strong anti-electromagnetic interference ability, small transmission loss, and can be transmitted over long distances, and have very broad application scenarios. Compared with traditional sensors, optical fiber sensors are light in weight and small in size, and these characteristics enable them to still work normally in extreme environments such as high toxicity, high temperature, strong electromagnetic interference, large electric noise and strong corrosion, and exhibit their irreplaceable role. The basic principle of the optical fiber sensor is that the change of external parameters such as temperature, humidity, strain, refractive index, pressure, magnetic field, current and other physical parameters affects the change of the transmission light characteristics of the optical fiber or the microstructure made of the optical fiber, such as intensity, wavelength, frequency or phase, and then the change of the output spectrum is demodulated to obtain the related information of the measured physical parameter. With the increasing demand for detection accuracy and multi-parameter synchronous measurement in the fields of industrial monitoring and biological medicine, there is still room for improvement in the sensitivity, anti-cross interference ability and stability of the existing optical fiber sensor. SUMMARY
[0003] The purpose of the present application is to provide an optical fiber sensor and a preparation method thereof to solve the problems in the background art.
[0004] To achieve the above purpose, the present application provides an optical fiber sensor, which comprises an optical fiber body, a cascaded F-P cavity structure, a metal reinforcing layer and a sensitive material coating.
[0005] The optical fiber body adopts a splicing structure of a single-mode optical fiber-a tapered hollow-core optical fiber-a single-mode optical fiber, wherein the length of the tapered hollow-core optical fiber is 6-10mm and the waist diameter is 30-50μm.
[0006] The cascaded F-P structure comprises a sensing cavity and a reference cavity arranged on the tapered hollow-core optical fiber.
[0007] The metal reinforcing layer comprises a silver film and a gold nanorod array arranged on the surface of the tapered hollow-core optical fiber in sequence, the thickness of the silver film is 30-50nm, the length-diameter ratio of the gold nanorod is 3:1-5:1, and the diameter is 40-60nm.
[0008] The sensitive material coating includes a polydimethylsiloxane (PDMS) film coated on the surface of the sensing cavity and a polyvinyl alcohol (PVA) film coated on the surface of the gold nanorod array, the thickness of the PDMS film is 3-7 microns, and the concentration of the PVA film is 2-4 wt%.
[0009] Preferably, the taper region length of the tapered coreless fiber is 8 mm, and the waist diameter is 40 microns.
[0010] Preferably, the sensing cavity is arranged in the middle of the tapered coreless fiber, the reference cavity is arranged on the right side of the sensing cavity, the sensing cavity is a micro-groove structure filled with ultraviolet glue, the cavity length is 100-200 microns, the reference cavity is an air cavity formed by fusion of a capillary tube and a single-mode optical fiber, the cavity length is 150-250 microns, and the difference between the free spectral ranges of the sensing cavity and the reference cavity is 0.3-0.7 nm.
[0011] Preferably, the cavity length of the sensing cavity is 150 microns, the cavity length of the reference cavity is 200 microns, and the difference between the free spectral ranges of the two is 0.5 nm.
[0012] Preferably, the thickness of the silver film is 40 nm, the aspect ratio of the gold nanorod is 4:1, the diameter is 50 nm, the thickness of the PDMS film is 5 microns, and the concentration of the PVA film is 3 wt%.
[0013] The application also provides a preparation method of the optical fiber sensor, which comprises the following steps:
[0014] S1, select a single-mode optical fiber and a coreless fiber, cut them into 30 cm long sections, and clean them with alcohol and deionized water in sequence, and dry them for standby;
[0015] S2, sequentially splice the single-mode optical fiber-coreless fiber-single-mode optical fiber, place the prepared fiber splicing structure in a fiber fusion machine, place the coreless fiber in the splicing structure in the center of the fiber fusion machine, discharge the coreless fiber by using the discharge function of the fiber fusion machine, and stretch the splicing structure to the two sides at the same time, to form a structure with a taper region length of 6-10 mm and a waist diameter of 30-50 microns;
[0016] S3, manufacture the sensing cavity and the reference cavity on the tapered coreless fiber prepared in step S2;
[0017] S4, deposit a silver film on the surface of the tapered coreless fiber by using a magnetron sputtering method, to form a silver film with a thickness of 30-50 nm, and prepare gold nanorods by using an electrochemical method, and fix the gold nanorods on the surface of the silver film by using a PVA transfer method, to form a gold nanorod array;
[0018] S5, coating PDMS on the surface of the sensing cavity, drying at 80-100 DEG C for 1-3 hours to form a 3-7 mu m thick PDMS film, and coating a 2-4 wt% PVA solution on the surface of the gold nanorod array, drying at 50-70 DEG C for 0.5-2 hours to form a PVA film.
[0019] Preferably, the preparation process of the sensing cavity in step S3 is as follows: a micro groove with a depth of 50-80 mu m is etched in the middle of the tapered fiber by femtosecond laser, then the micro groove is filled with UV glue, and the UV glue is cured by irradiation with a 365 nm UV lamp for 5-10 minutes to form the sensing cavity.
[0020] Preferably, the preparation process of the reference cavity in step S3 is as follows: first, the selected quartz capillary is fusion spliced with the single-mode optical fiber on the right side of the tapered fiber at a position 1-3 mm to the right of the sensing cavity, after the fusion splicing is completed, the quartz capillary is cut to an appropriate length using an optical fiber cutting knife, and after the cutting is completed, the other end of the quartz capillary is aligned with another single-mode optical fiber, and the second fusion splicing is completed using the same fusion splicing parameters to form the reference cavity.
[0021] Preferably, the inner diameter of the quartz capillary is 75 mu m.
[0022] Therefore, the optical fiber sensor and the preparation method thereof have the following beneficial effects:
[0023] (1) The evanescent field effect is enhanced by using the tapered fiber structure, the sensitivity is amplified by combining the vernier effect of the cascaded F-P cavity, and the interaction between light and matter is further enhanced by the surface plasmon resonance effect of the gold nanorod, thereby improving the detection sensitivity;
[0024] (2) The regional selectivity of the special structure optical fiber is used in combination with the response characteristics of different sensitive materials to realize the synchronous measurement of temperature, humidity and refractive index. The cross interference between parameters is effectively reduced by the spectral frequency division characteristics of the cascaded F-P cavity and the selective response of the gold nanorod;
[0025] (3) The mature processes such as femtosecond laser processing and magnetron sputtering are used to realize the firm combination of the gold nanorod and the surface of the optical fiber, and the stability is significantly improved;
[0026] (4) All functional structures are integrated in a single optical fiber, and the overall length is controlled within 5 cm to meet the miniaturization application scene requirements.
[0027] The technical solutions of the present application will be further described in detail below with reference to the drawings and examples. BRIEF DESCRIPTION OF DRAWINGS
[0028] Figure 1 Fig. 1 is a structural schematic diagram of the optical fiber sensor of the present application;
[0029] Figure 2 This is a flowchart of a method for fabricating an optical fiber sensor according to the present invention. Detailed Implementation
[0030] The following detailed description of embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.
[0031] Please see Figure 1 An optical fiber sensor includes an optical fiber body, a cascaded FP cavity structure, a metal reinforcement layer, and a sensitive material coating.
[0032] The optical fiber body adopts a splicing structure of single-mode fiber-tapered coreless fiber-single-mode fiber, wherein the tapered section length of the tapered coreless fiber is 6-10mm and the waist diameter is 30-50μm;
[0033] The cascaded FP structure includes a sensing cavity and a reference cavity set on a tapered coreless optical fiber;
[0034] The metal reinforcement layer comprises a silver film and a gold nanorod array sequentially disposed on the surface of a tapered coreless optical fiber. The silver film has a thickness of 30-50 nm, and the gold nanorods have an aspect ratio of 3:1-5:1 and a diameter of 40-60 nm.
[0035] The sensitive material coating includes a polydimethylsiloxane (PDMS) film coated on the surface of the sensing cavity and a polyvinyl alcohol (PVA) film coated on the surface of the gold nanorod array. The PDMS film has a thickness of 3-7 μm and the PVA film has a concentration of 2-4 wt%.
[0036] like Figure 2 As shown, a method for fabricating an optical fiber sensor includes the following steps:
[0037] S1. Select single-mode fiber and coreless fiber, cut them into 30cm long segments, clean them with alcohol and deionized water in turn using ultrasonic cleaning, and then dry them for later use.
[0038] S2. The single-mode fiber-coreless fiber-single-mode fiber are thermally spliced in sequence. The fabricated fiber splicing structure is placed in the fiber fusion splicer, and the coreless fiber in the splicing structure is placed in the center of the fiber fusion splicer. The coreless fiber is discharged using the discharge function of the fiber fusion splicer, and the splicing structure is stretched to both sides at the same time to form a structure with a cone length of 6-10mm and a cone waist diameter of 30-50μm.
[0039] S3. Fabricate a sensing cavity and a reference cavity on the tapered coreless optical fiber fabricated in step S2;
[0040] S4. A silver film with a thickness of 30-50 nm is deposited on the surface of a tapered coreless optical fiber by magnetron sputtering. Gold nanorods are then prepared by electrochemical method and fixed on the surface of the silver film by PVA transfer method to form a gold nanorod array.
[0041] S5. Coat the surface of the sensing cavity with PDMS and dry at 80-100℃ for 1-3 hours to form a PDMS film with a thickness of 3-7μm. Coat the surface of the gold nanorod array with 2-4wt% PVA solution and dry at 50-70℃ for 0.5-2 hours to form a PVA film.
[0042] Based on the structure and fabrication method of the fiber optic sensor described above, this embodiment uses the following experiments to verify its sensitivity, multi-parameter synchronous detection, anti-cross-interference performance, and stability.
[0043] Example 1
[0044] Experimental conditions:
[0045] Refractive index test: Prepare a sodium chloride solution of 1.329-1.379 RIU (concentration 0-20 wt%), in 0.01 RIU intervals, and calibrate using an Abbe refractometer.
[0046] Temperature test: A WHTH-80L constant temperature chamber was used, with a temperature range of 30-90℃, a step size of 10℃, and a holding time of 30 minutes until the temperature stabilized.
[0047] Humidity test: Use a constant temperature and humidity chamber with a humidity range of 30-80%RH, a step size of 10%RH, and a constant temperature of 40℃.
[0048] Testing equipment: AQ6370D spectrometer (resolution 0.02nm), FL-ASE broadband light source (1250-1650nm).
[0049] Experimental procedure:
[0050] Refractive index response test: Immerse the fiber optic sensor in sodium chloride solutions of different concentrations, record the resonant wavelength drift, and take the average value for each concentration in 3 measurements.
[0051] Temperature response test: The fiber optic sensor was placed in a constant temperature chamber and the temperature was increased from 30°C to 90°C. The spectrum was recorded after each temperature increase, and the wavelength shift was calculated.
[0052] Humidity response test: In a constant temperature and humidity chamber, the RH was increased from 30% to 80% and the spectral changes were recorded after each humidity stabilization.
[0053] Experimental results:
[0054] Detection parameter Measurement range Sensitivity Single structure contrast improvement Refractive index 1.329-1.379 RIU 3500 nm / RIU 42% (vs. LPG) Temperature 30-90℃ -25 nm / °C 150% (vs. single F-P cavity) Humidity 30-80% RH 0.8 nm / % RH 60% (vs. PVA coating)
[0055] Results analysis:
[0056] The significant improvement in refractive index sensitivity stems from: evanescent field enhancement of tapered coreless fiber (40μm tapered waist) (2.3 times stronger than ordinary fiber) + LSPR effect of gold nanorods (3 times amplification of local electric field) + vernier effect of cascaded FP cavity (10 times amplification).
[0057] The improved temperature sensitivity is due to: PDMS film (thermal expansion coefficient 310×10). -6 / ℃) and UV adhesive (thermophoto coefficient 8×10) -4 The synergistic effect of ( / ℃) combined with the vernier effect of the cascaded cavity amplification.
[0058] The increased humidity sensitivity is due to the PVA film absorbing water and swelling (swelling rate 1.2% / %RH), which changes the refractive index around the gold nanorods, and the LSPR effect amplifies the spectral drift.
[0059] Example 2
[0060] Experimental conditions:
[0061] The effect of humidity (30-80% RH) on the measurement of refractive index (1.333-1.353 RIU) was tested at a fixed temperature of 40℃.
[0062] The effect of temperature (30-70℃) on humidity measurement was tested at a fixed humidity of 50% RH.
[0063] Fourier bandpass filtering is used to separate the spectral signals of each cavity, and a sensitivity matrix is constructed:
[0064]
[0065] Where Δλ1, Δλ2, and Δλ3 represent spectral drift; ΔT represents temperature change; ΔRH represents relative humidity change; and Δn represents refractive index change of the medium under test.
[0066] Experimental procedure:
[0067] Temperature (30→50℃), humidity (50%→70%RH), and refractive index (1.333→1.343RIU) were simultaneously changed, and the spectral drift under the coupling of the three parameters was recorded.
[0068] By using sensitivity matrix decoupling, the deviation between the actual measured value and the theoretical value is calculated.
[0069] Experimental results:
[0070] Temperature measurement error: ±0.1℃ (theoretical change 20℃, actual measurement 19.9±0.1℃).
[0071] Humidity measurement error: ±0.3%RH (theoretical variation 20%RH, actual measurement 19.8±0.3%RH).
[0072] Refractive index measurement error: ±0.0002RIU (theoretical variation 0.01RIU, actual measurement 0.0098±0.0002RIU).
[0073] Cross sensitivity: Temperature interference to humidity measurement <0.1%RH / ℃, humidity interference to refractive index measurement <0.0001RIU / %RH.
[0074] Results analysis:
[0075] Multi-parameter detection is achieved through structural partitioning: the main response temperature of FPI1 (UV adhesive + PDMS), the main response humidity of gold nanorod + PVA layer, and the main response refractive index of the tapered region.
[0076] Fourier filtering technology effectively separates the spectral signals of each cavity and avoids cross-interference, achieving a 10-fold improvement over the traditional parallel structure (cross-interference >1%).
[0077] Example 3
[0078] Experimental conditions:
[0079] Environment: Temperature 40℃±0.5℃, humidity 50%RH±2%RH, continuous monitoring for 100 hours.
[0080] Monitoring parameters: resonant wavelength drift corresponding to a refractive index of 1.333 RIU (deionized water).
[0081] Experimental procedure:
[0082] 1. Fix the sensor in the flow cell and continuously pass deionized water through it to maintain constant temperature and humidity.
[0083] 2. Record the spectrum every hour and calculate the resonant wavelength fluctuation.
[0084] Experimental results:
[0085] Maximum wavelength drift within 100 hours: 0.42 nm, corresponding to a refractive index measurement error of <0.0002 RIU.
[0086] Temperature drift contribution: 0.12nm (28.6%), humidity drift contribution: 0.08nm (19.0%), mechanical stability drift: 0.22nm (52.4%).
[0087] Results analysis:
[0088] The stability is attributed to: magnetron sputtered silver film (adhesion > 5 N / cm) 2The PVA transfer method using gold nanorods (film thickness uniformity ±2nm) avoids the shedding of nanomaterials.
[0089] Compared to traditional coated sensors (drift >2nm after 100 hours), this structure improves stability by 4.8 times, meeting the needs of long-term monitoring.
[0090] In summary, the fiber optic sensor in this embodiment achieves high sensitivity (3500 nm / RIU refractive index, -25 nm / ℃ temperature, 0.8 nm / %RH humidity) through multi-mechanism collaboration, representing a 40%-150% improvement over a single-structure design. Multi-parameter synchronous detection cross-interference is <0.1%, meeting the measurement requirements of complex environments. A 100-hour stability test proves the structural reliability, making it suitable for long-term monitoring. The above embodiments fully verify the beneficial effects of the composite fiber optic sensor in terms of sensitivity, multi-parameter detection, stability, and miniaturization. The data are consistent with the theoretical design and meet practical application requirements.
[0091] Therefore, the present invention employs the above-mentioned fiber optic sensor and its preparation method to form a synergistically enhanced sensing system, which simultaneously takes into account both high sensitivity and multi-parameter detection capability.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. An optical fiber sensor, characterized by: The fiber body, the cascaded F-P cavity structure, the metal reinforcing layer and the sensitive material coating layer are included. The fiber body adopts a splicing structure of single-mode fiber-tapered coreless fiber-single-mode fiber, wherein the taper region length of the tapered coreless fiber is 6-10 mm, and the taper waist diameter is 30-50 µm. The cascaded F-P structure includes a sensing cavity and a reference cavity arranged on the tapered coreless fiber. The metal reinforcing layer includes a silver film and a gold nanorod array arranged on the surface of the tapered coreless fiber in sequence, the thickness of the silver film is 30-50 nm, the length-diameter ratio of the gold nanorod is 3:1-5:1, and the diameter is 40-60 nm. The sensitive material coating layer includes a polydimethylsiloxane (PDMS) film coated on the surface of the sensing cavity and a polyvinyl alcohol (PVA) film coated on the surface of the gold nanorod array, the thickness of the PDMS film is 3-7 µm, and the concentration of the PVA film is 2-4 wt%.
2. A fiber optic sensor according to claim 1, characterized in that: The taper region length of the tapered coreless fiber is 8 mm, and the taper waist diameter is 40 µm.
3. A fiber optic sensor according to claim 1, characterized in that: The sensing cavity is arranged at the middle part of the tapered coreless fiber, and the reference cavity is arranged at the right side of the sensing cavity, the sensing cavity is a micro groove structure filled with ultraviolet glue, and the cavity length is 100-200 µm. The reference cavity is an air cavity formed by fusion of a capillary tube and a single-mode fiber, the cavity length is 150-250 µm, and the difference between the free spectral ranges of the sensing cavity and the reference cavity is 0.3-0.7 nm.
4. A fibre optic sensor according to claim 3, characterised in that: The cavity length of the sensing cavity is 150 µm, the cavity length of the reference cavity is 200 µm, and the difference between the free spectral ranges of the two is 0.5 nm.
5. The fiber optic sensor of claim 1, wherein: The thickness of the silver film is 40 nm, the length-diameter ratio of the gold nanorod is 4:1, and the diameter is 50 nm; the thickness of the PDMS film is 5 µm, and the concentration of the PVA film is 3 wt%.
6. A method of manufacturing an optical fiber sensor as claimed in any one of the claims 1-5, characterized in that, The method comprises the following steps: S1, select single-mode fiber and coreless fiber, cut into 30 cm long sections, ultrasonic clean with alcohol and deionized water in sequence, and dry for standby use; S2, splice the single-mode fiber-coreless fiber-single-mode fiber in sequence, place the prepared fiber splicing structure in the fiber fusion machine, place the coreless fiber in the splicing structure in the center of the fiber fusion machine, discharge the coreless fiber by using the discharge function of the fiber fusion machine, and stretch the splicing structure to the two sides at the same time to form a structure with a taper region length of 6-10 mm and a taper waist diameter of 30-50 µm; S3, prepare the sensing cavity and the reference cavity on the tapered coreless fiber prepared in step S2; S4, deposit a silver film on the surface of the tapered coreless fiber by using magnetron sputtering to form a silver film with a thickness of 30-50 nm, and prepare gold nanorods by electrochemical method, and fix the gold nanorods on the surface of the silver film by PVA transfer method to form a gold nanorod array; S5, coat PDMS on the surface of the sensing cavity, dry at 80-100 ℃ for 1-3 hours to form a PDMS film with a thickness of 3-7 µm, and coat a 2-4 wt% PVA solution on the surface of the gold nanorod array, dry at 50-70 ℃ for 0.5-2 hours to form a PVA film.
7. A method of making an optical fiber sensor according to claim 6, wherein, In step S3, the preparation process of the sensing cavity is as follows: a micro groove with a depth of 50-80 µm is etched in the middle part of the tapered coreless fiber by using femtosecond laser, then ultraviolet glue is filled in the micro groove, and then the sensing cavity is formed by irradiating with a 365 nm ultraviolet lamp for 5-10 minutes for curing.
8. A method of making an optical fiber sensor according to claim 6, wherein: The preparation process of the reference cavity in step S3 is as follows: first, the selected one end of the quartz capillary is fused with the single-mode optical fiber on the right side of the tapered fiber, and the fusion position is located at 1-3 mm on the right side of the sensing cavity; after the fusion is completed, the quartz capillary is cut to an appropriate length by using an optical fiber cutting knife; after the cutting is completed, the other end of the quartz capillary is aligned with another single-mode optical fiber, and the second fusion is completed by using the same fusion parameters, so that the reference cavity is formed.
9. A method of making an optical fiber sensor according to claim 8, wherein: The inner diameter of the quartz capillary is 75 μm.
Citation Information
Cited By
Separated optical fiber multi-parameter sensing device, system and method
CN122329380A
